2015
DOI: 10.1097/md.0000000000002082
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-MIBI Lung Scintigraphy in the Assessment of Pulmonary Involvement in Interstitial Lung Disease and Its Comparison With Pulmonary Function Tests and High-Resolution Computed Tomography

Abstract: The differentiation of active inflammatory processes from an inactive form of the disease is of great value in the management of interstitial lung disease (ILD). The aim of this investigation was to assess the efficacy of 99mTc-methoxy-isobutyl-isonitrile (99mTc-MIBI) scans in distinguishing the severity of the disease compared to radiological and clinical parameters.In total, 19 known cases of ILD were included in this study and were followed up for 1 year. Five patients without lung disease were considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, it could go back to the chemical characteristics of radiopharmaceuticals, the cationic charge, the lipophilic properties, and the negative transmembrane potentials generated in the cytoplasm and mitochondria of metabolically active cells. [10]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it could go back to the chemical characteristics of radiopharmaceuticals, the cationic charge, the lipophilic properties, and the negative transmembrane potentials generated in the cytoplasm and mitochondria of metabolically active cells. [10]…”
Section: Discussionmentioning
confidence: 99%
“…99mTc-MIBI is taken up in vivo by tissues with abundant mitochondria, such as cardiac muscle and malignancies. Although cancerous tissues in the lungs have been shown to have abnormal 99mTc-MIBI activity, pulmonary absorption in non-neoplastic situations appears to be rare [66]. Despite the promising results from preclinical and pilot trials, this drug is not yet used in routine clinical practice.…”
Section: M Tc-mibi Lung Scintigraphymentioning
confidence: 99%
“…To further expand this point, we would like to suggest that few scintigraphic studies in the management of ILD have been performed. We assessed the clinical significance of 99mTc-IgG and 99mTc-MIBI scintigraphy in the assessment of such patients in prospective cohort studies (2,3). We demonstrated that both lung scans can distinguish the severity of pulmonary involvement even in early views.…”
mentioning
confidence: 99%